2009
DOI: 10.1063/1.3194797
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanisms of oxygen atoms in the O(PJ3) state from the 157nm photoirradiation of amorphous water ice at 90K

Abstract: Desorption of ground state O͑ 3 P J=2,1,0 ͒ atoms following the vacuum ultraviolet photolysis of water ice in the first absorption band was directly measured with resonance-enhanced multiphoton ionization ͑REMPI͒ method. Based on their translational energy distributions and evolution behavior, two different formation mechanisms are proposed: One is exothermic recombination reaction of OH radicals, OH + OH → H 2 O+O͑ 3 P J ͒ and the other is the photodissociation of OH radicals on the surface of amorphous solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…Photodesorbed O͑ 3 P J=2,1,0 ͒ atoms were ionized by the 2 + 1 REMPI transition via the O͑ 3 P J -3 P J ͒ transition at 225.6-226.4 nm. 17 We tried to search for REMPI signals of oxygen molecules in the higher electronically excited states, i.e., b 1 ⌺ g + , c 1 ⌺ u − , and 5 ͟ g using the REMPI transitions reported by Morrill et al 32 and Slanger and Copeland, 33 but no evidence for these products was obtained.…”
Section: A Apparatus and Preparation Of Icementioning
confidence: 99%
See 2 more Smart Citations
“…Photodesorbed O͑ 3 P J=2,1,0 ͒ atoms were ionized by the 2 + 1 REMPI transition via the O͑ 3 P J -3 P J ͒ transition at 225.6-226.4 nm. 17 We tried to search for REMPI signals of oxygen molecules in the higher electronically excited states, i.e., b 1 ⌺ g + , c 1 ⌺ u − , and 5 ͟ g using the REMPI transitions reported by Morrill et al 32 and Slanger and Copeland, 33 but no evidence for these products was obtained.…”
Section: A Apparatus and Preparation Of Icementioning
confidence: 99%
“…The translational and internal energy distributions of OH͑v =0,1͒ radicals and O͑ 1 D and 3 P͒ atoms were previously measured following 157 nm photodissociation of ASW. [15][16][17] For the O͑ 3 P͒ production, two different formation mechanisms were proposed: the exothermic recombination reaction of OH and the photodissociation of OH on the ASW surface, 17 OH + OH → H 2 O + O͑ 3 P͒, ⌬H = − 67 kJ mol −1 , ͑3͒…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,17,18 O( 3 P J ) formation by 157-nm irradiation of 1500 L amorphous solid ASW at 90 K has been measured previously by Hama et al, who found that four Maxwell-Boltzmann components with translational temperatures of 5000, 1300, 300, and 100 K fit their data. 11 The 5000 K component, which was attributed to hydroxyl dissociation, increased significantly with 30 min of prior irradiation when compared to freshly dosed ASW. 11 When compared to the time-of-flight (TOF) spectrum of O( 3 P J ) from ASW, the TOF spectrum for O( 3 P J ) from H 2 O 2 was found to be roughly the same shape but twice as intense.…”
Section: Introductionmentioning
confidence: 94%
“…Because photodissociation of water is such an important process in atmospheric, interstellar, and planetary chemistry, it has been studied extensively. [11][12][13][14][15][16] Even when the primary experimental goal is to measure photodesorption of water, a significant amount of photodissociation occurs and complicates the interpretation of measured water removal cross sections. 9,17,18 O( 3 P J ) formation by 157-nm irradiation of 1500 L amorphous solid ASW at 90 K has been measured previously by Hama et al, who found that four Maxwell-Boltzmann components with translational temperatures of 5000, 1300, 300, and 100 K fit their data.…”
Section: Introductionmentioning
confidence: 99%